Implementation Of Smart Techno Parenting in Shaping Children's Character to Face the Industry 5.0 Era - Purba, Nursenta Dahliana; Putri Nome, Davi Cristika (Jurnal Didaskalia, 2024)
The use of gadgets as playmates for children has become increasingly common among modern parents. This trend has led to a shift in the parental role as play companions, especially during the developmental stage of children aged 1-5 years, known as the "golden age." This period is critical for the growth of intellectual, emotional, and spiritual intelligence, which significantly influences a child's future development. This study aims to examine the importance of parental involvement during the golden age by implementing a technology-based parenting approach (smart techno parenting) to support the development of a child's character, personality, and cognitive abilities. The research employs a literature review method, gathering data from relevant sources to understand the concept and application of smart techno parenting. Smart techno parenting has proven to be a wise approach for parents to protect, educate, discipline, and guide their children amid the influence of technology. Parents adopting this method must continuously learn and serve as primary role models for their children. Smart techno parenting is an effective strategy for optimizing a child's development during the golden age, enabling parents to act as intelligent companions who utilize technology wisely without neglecting the child's fundamental needs for play, learning, and direct interaction.